Pengaruh karakteristik individual dalam pembuatan keputusan berbasis etis berdasarkan perkembangan moral cognitive melalui intervening deontologi moral evaluation auditor - Zulman '; Emrinaldi Nur DP; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to find out the effect of time pressure, audit risk, cognitive moral development and deontology moral evaluation into audit procedure’s premature sign off from individual characteristic’side in making ethical decision. This research used premature stopping attitude of audit procedure as the dependence. Recently, this unethical attitude seems to be risky thing because it indicates that auditors are not consistent about their responsible and ethics.Population of this research is all independent auditors working in KAP in Pekanbaru, Padang and Batam. While sample are those who work in KAP kotaPekanbaru, Padang and Batam. Sampling was done by purposive sampling method. The number of sample used are 69 respondents. Data is analyzed by PLS analysis technique (Partial Least Squeare) using SmartPLS software.Result shows that time pressure has significant effect to audit procedure’s premature sign off, cognitive moral development and deontology moral evaluation have non significant negative effect to audit procedure’s premature sign off. Beside that, there is also a significant connection between somebody’s cognitive moral development and deontology moral evaluation. Fifth TStatistic tes simultaneously has no effect to audit procedure’s premature sign off. Only 23,8% variability construct premature stopping attitude of audit procedure, and the rest 76.2% explaineby other variable outside this research.Key word: premature sign off, time pressure, audit risk, cognitive moral development, deontology moral evaluation.